A novel one-step synthesized and dopant-free hole transport material for efficient and stable perovskite solar cells. Issue 42 (12th October 2016) - Zhao, Xiaoming; Zhang, Fei; Yi, Chenyi; Bi, Dongqin; Bi, Xiangdong; Wei, Peng; Luo, Jingshan; Liu, Xicheng; Wang, Shirong; Li, Xianggao; Zakeeruddin, Shaik Mohammed; Grätzel, Michael
Abstract : A simple one-step synthesized hole transport material was developed for dopant-free perovskite solar cells with a PCE of 15.4%. Abstract : A hole transport material ST1 was synthesized by a one-step Heck reaction. Compared to Spiro-OMeTAD, perovskite solar cells with ST1 exhibit a remarkable overall power conversion efficiency of 15.4% without the use of any dopants and additives, which is comparable to that of the devices based on doped Spiro-OMeTAD (16.3%) and present better stability during a four week aging test.